ACTIVITY-BASED PROBES TO UTILIZE THE PROTEOLYTIC ACTIVITY OF CATHEPSIN G IN BIOLOGICAL SAMPLES - Burster, Timo; Gärtner, Fabian; Knippschild, Uwe; Zhanapiya, Anuar (Front. Chem., 2021)
Neutrophils, migrating to the site of infection, are able to release serine proteases after being activated. These serine proteases comprise cathepsin G (CatG), neutrophil elastase protease 3 (PR3), and neutrophil serine protease 4 (NSP4). A disadvantage of the uncontrolled proteolytic activity of proteases is the outcome of various human diseases, including cardiovascular diseases, thrombosis, and autoimmune diseases. Activity-based probes (ABPs) are used to determine the proteolytic activity of proteases, containing a set of three essential elements: Warhead, recognition sequence, and the reporter tag for detection of the covalent enzyme activity–based probe complex. ...
Keywords: immune cells; serine proteases; activity-based probes